Celebrating the Life of Dr. Andrew “Andy” Bakun - Francisco E. Werner; Jürgen Alheit; Vera Agostini; Steven Bograd; John Field; Anne B. Hollowed; Salvador Lluch‐Cota; Nate Mantua; R. Ian Perry; Ryan R. Rykaczewski; Frank Schwing; Justin Suca (Fisheries Oceanography, 2026)

Comment on “Tianeptine Exposures Reported to United States Poison Centers, 2015–2023” - James B. Leonard; Perry E. Rosen; Christopher J. Counts (Journal of Medical Toxicology, 2025)

Quantifying coral reef carbonate budgets: a comparison between ReefBudget and CoralNet - Sivajyodee Sannassy Pilly; Joseph E. Townsend; Cut Aja Gita Alisa; Tries B. Razak; Ronan C. Roche; John R. Turner; Stephen Chan; David J. Kriegman; Andreas J. Andersson; Chris T. Perry; Ines D. Lange; Travis A. Courtney (Coral Reefs, 2025)
Calcium carbonate production constitutes one of the core processes that drive coral reef ecosystem functioning and can be assessed using in-water or image-based survey methods, which have not previously been compared. This study compares carbonate production estimates from in-water ReefBudget surveys and image-based CoralNet analyses in Puerto Rico, Indonesia, and Chagos Archipelago. Methods were compared for different regions (Western Atlantic and Indo-Pacific), reef settings (low and high coral cover), CoralNet calcification versions (v1 and v2), and input metrics (regional vs. local coral growth rates). We show similar gross carbonate production estimates between methods, indicating that area-normalised scaling of calcification rates and assumptions about colony size and rugosity employed in CoralNet produce comparable estimates to ReefBudget surveys. Divergences in carbonate production estimates are potentially driven by differences in survey methods (reef contour measurements vs. planar imagery) and survey effort, which affect calcifier cover estimates, particularly at low coral cover sites. Local versus regional growth rate comparisons suggest site-specific factors can influence accuracy more than method choice. Our findings suggest that image-based methods can allow rapid reef-scale calcification estimates from photo or video imagery. These methods, combined with machine learning substrate classification algorithms, can estimate both benthic cover and carbonate production over larger reef areas and can be applied to historically collect benthic cover data to track carbonate production trends. We encourage researchers to recognise situation-specific differences in methodologies and select the one most suitable for their specific study site, required level of accuracy, and time constraints for fieldwork and image analysis.

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

National-scale antimicrobial resistance surveillance in wastewater: A comparative analysis of HT qPCR and metagenomic approaches - Margaret E. Knight; Gordon Webster; William B. Perry; Amy Baldwin; Laura Rushton; Daniel A. Pass; Gareth Cross; Isabelle Durance; Windi Muziasari; Peter Kille; Kata Farkas; Andrew J. Weightman; et al. (Water Research, 2024)

Producing 3D radargrams from orbital radar sounding data at Mars: History, results, methods, lessons and plans - Frederick J. Foss; Nathaniel E. Putzig; Bruce A. Campbell; Stewart A. Levin; Matthew R. Perry; John W. Holt; Michael S. Christoffersen; Isaac B. Smith; Gareth A. Morgan; Aaron T. Russell (Icarus, 2024)

Three-dimensional imaging of martian glaciated terrain using Mars Reconnaissance Orbiter Shallow Radar (SHARAD) observations - Matthew R. Perry; Aaron T. Russell; Megan B. Russell; Frederick J. Foss; Frank C. Chuang; Gareth A. Morgan; Zachary M. Bain; Bruce A. Campbell; Nathaniel E. Putzig (Icarus, 2024)

Science results from sixteen years of MRO SHARAD operations - Nathaniel E. Putzig; Roberto Seu; Gareth A. Morgan; Isaac B. Smith; Bruce A. Campbell; Matthew R. Perry; Marco Mastrogiuseppe (Icarus, 2024)

Digital strategies for nitrogen management in grain production systems: lessons from multi-method assessment using on-farm experimentation - A. F. Colaço; B. M. Whelan; R. G. V. Bramley; J. Richetti; M. Fajardo; A. C. McCarthy; E. M. Perry; A. Bender; S. Leo; G. J. Fitzgerald; R. A. Lawes (Precision Agriculture, 2024)
During the past few decades, a range of digital strategies for Nitrogen (N) management using various types of input data and recommendation frameworks have been developed. Despite much research, the benefits accrued from such technology have been equivocal. In this work, thirteen methods for mid-season N recommendations in cereal production systems were evaluated simultaneously, ranging from simple mass balance through to non-mechanistic approaches based on machine learning. To achieve this, an extensive field research program was implemented, comprising twenty-one N strip trials implemented in wheat and barley fields across Australia over four cropping seasons. A moving window regression approach was used to generate crop response functions to applied N and calculate economically optimal N rates along the length of the strips. The N recommendations made using various methods were assessed based on the error against the optimal rate and expected profitability. The root mean squared error of the recommendations ranged from 15 to 57 kg/ha. The best performing method was a data-driven empirical strategy in which a multivariate input to characterise field and season conditions was abundantly available and used to predict optimal N rates using machine learning. This was the only approach with potential to substantially outperform the existing farmer management, reducing the recommendation error from 42 to 15 kg/ha and improving profitability by up to A$47/ha. Despite being reliant on extensive historical databases, such a framework shows a promising pathway to drive production systems closer towards season- and site-specific economically optimum recommendations. Automated on-farm experimentation is a key enabler for building the necessary crop response databases to run empirical data-driven decision tools.

Treatment of acid mine drainage and chromium (VI) removal using synthesised chitosan composites blended with kenaf fibre and γ-Fe2O3 nanoparticles - C. N. Nkuna; E. R. Sadiku; G. Perry; B. Oboirien; M. K. Dludlu; C. Thompson (International Journal of Environmental Science and Technology, 2023)

Coexistence between similar invaders: The case of two cosmopolitan exotic insects - Matthew B. Arnold; Michael Back; Michael Daniel Crowell; Nageen Farooq; Prashant Ghimire; Omon A. Obarein; Kyle E. Smart; Trixie Taucher; Erin VanderJeugdt; Kayla I. Perry; Douglas A. Landis; Christie A. Bahlai (Ecology, 2023)
Biological invasions are usually examined in the context of their impacts on native species. However, few studies have examined the dynamics between invaders when multiple exotic species successfully coexist in a novel environment. Yet, long‐term coexistence of now established exotic species has been observed in North American lady beetle communities. Exotic lady beetles Harmonia axyridis and Coccinella septempunctata were introduced for biological control in agricultural systems and have since become dominant species within these communities. In this study, we investigated coexistence via spatial and temporal niche partitioning among H. axyridis and C. septempunctata using a 31‐year data set from southwestern Michigan, USA. We found evidence of long‐term coexistence through a combination of small‐scale environmental, habitat, and seasonal mechanisms. Across years, H. axyridis and C. septempunctata experienced patterns of cyclical dominance likely related to yearly variation in temperature and precipitation. Within years, populations of C. septempunctata peaked early in the growing season at 550 degree days, while H. axyridis populations grew in the season until 1250 degree days and continued to have high activity after this point. C. septempunctata was generally most abundant in herbaceous crops, whereas H. axyridis did not display strong habitat preferences. These findings suggest that within this region H. axyridis has broader habitat and abiotic environmental preferences, whereas C. septempunctata thrives under more specific ecological conditions. These ecological differences have contributed to the continued coexistence of these two invaders. Understanding the mechanisms that allow for the coexistence of dominant exotic species contributes to native biodiversity conservation management of invaded ecosystems.

A Case Study of Large Floodplain River Restoration: Two Decades of Monitoring the Merwin Preserve and Lessons Learned through Water Level Fluctuations and Uncontrolled Reconnection to a Large River - Levi E. Solomon; Andrew F. Casper; Kristopher A. Maxson; James T. Lamer; Trent W. Ford; K. Douglass Blodgett; Tharran Hobson; Denim Perry; Nathan T. Grider; Rob B. Hilsabeck; Thad R. Cook; Kevin S. Irons; et al. (Wetlands, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The Mechanical Response and Tolerance of the Anteriorly-Tilted Human Pelvis Under Vertical Loading - R. S. Salzar; E. M. Spratley; K. A. Henderson; P. C. Greenhalgh; J. Z. Zhang; B. J. Perry; J. A. McMahon (Annals of Biomedical Engineering, 2021)

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Floral Odors and the Interaction between Pollinating Ceratopogonid Midges and Cacao - Sarah E. J. Arnold; Samantha J. Forbes; David R. Hall; Dudley I. Farman; Puran Bridgemohan; Gustavo R. Spinelli; Daniel P. Bray; Garvin B. Perry; Leroy Grey; Steven R. Belmain; Philip C. Stevenson (Journal of Chemical Ecology, 2019)
Most plant species depend upon insect pollination services, including many cash and subsistence crops. Plants compete to attract those insects using visual cues and floral odor which pollinators associate with a reward. The cacao tree, Theobroma cacao , has a highly specialized floral morphology permitting pollination primarily by Ceratopogonid midges. However, these insects do not depend upon cacao flowers for their life cycle, and can use other sugar sources. To understand how floral cues mediate pollination in cacao we developed a method for rearing Ceratopogonidae through several complete lifecycles to provide material for bioassays. We carried out collection and analysis of cacao floral volatiles, and identified a bouquet made up exclusively of saturated and unsaturated, straight-chain hydrocarbons, which is unusual among floral odors. The most abundant components were tridecane, pentadecane, ( Z )-7-pentadecene and ( Z )-8-heptadecene with a heptadecadiene and heptadecatriene as minor components. We presented adult midges, Forcipomyia sp. (subgen . Forcipomyia ) , Culicoides paraensis and Dasyhelea borgmeieri, with natural and synthetic cacao flower odors in choice assays. Midges showed weak attraction to the complete natural floral odor in the assay, with no significant evidence of interspecific differences. This suggests that cacao floral volatiles play a role in pollinator behavior. Midges were not attracted to a synthetic blend of the above four major components of cacao flower odor, indicating that a more complete blend is required for attraction. Our findings indicate that cacao pollination is likely facilitated by the volatile blend released by flowers, and that the system involves a generalized odor response common to different species of Ceratopogonidae.

Advocating for Science: Amici Curiae Brief of Wetland and Water Scientists in Support of the Clean Water Rule - Royal C. Gardner; Erin Okuno; Steph Tai; M. Siobhan Fennessy; Carol A. Johnston; Marinus L. Otte; Margaret Palmer; James E. Perry; Charles Simenstad; Benjamin R. Tanner; Dan Tufford; R. Eugene Turner; et al. (Wetlands, 2019)

The role of reforestation in carbon sequestration - L. E. Nave; B. F. Walters; K. L. Hofmeister; C. H. Perry; U. Mishra; G. M. Domke; C. W. Swanston (New Forests, 2019)

Linkage fine-mapping and QTLs affecting morpho-agronomic traits of a Mesoamerican × Andean RIL common bean population - Leonardo Corrêa da Silva; Thiago Lívio Pessoa Oliveira de Souza; Cosme Damião Cruz; Pedro Crescêncio Souza Carneiro; Fabyano Fonseca e Silva; Everaldo Gonçalves de Barros; Rosana Pereira Vianello; Carlos Eduardo Lazarini da Fonseca; Qijian Song; Perry B. Cregan; José Eustáquio de Souza Carneiro (Euphytica, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Arbuscular mycorrhizal fungi associated with Leptospermum scoparium (mānuka): effects on plant growth and essential oil content - Wisnu Adi Wicaksono; Catherine E. Sansom; E. Eirian Jones; Nigel B. Perry; Jana Monk; Hayley J. Ridgway (Symbiosis, 2018)

Wetlands In a Changing Climate: Science, Policy and Management - William R. Moomaw; G. L. Chmura; Gillian T. Davies; C. M. Finlayson; B. A. Middleton; Susan M. Natali; J. E. Perry; N. Roulet; Ariana E. Sutton-Grier (Wetlands, 2018)

The basis function approach for modeling autocorrelation in ecological data - Trevor J. Hefley; Kristin M. Broms; Brian M. Brost; Frances E. Buderman; Shannon L. Kay; Henry R. Scharf; John R. Tipton; Perry J. Williams; Mevin B. Hooten (Ecology, 2017)
Analyzing ecological data often requires modeling the autocorrelation created by spatial and temporal processes. Many seemingly disparate statistical methods used to account for autocorrelation can be expressed as regression models that include basis functions. Basis functions also enable ecologists to modify a wide range of existing ecological models in order to account for autocorrelation, which can improve inference and predictive accuracy. Furthermore, understanding the properties of basis functions is essential for evaluating the fit of spatial or time‐series models, detecting a hidden form of collinearity, and analyzing large data sets. We present important concepts and properties related to basis functions and illustrate several tools and techniques ecologists can use when modeling autocorrelation in ecological data.

Fresh Water Lens Persistence and Root Zone Salinization Hazard Under Temperate Climate - Sija F. Stofberg; Gualbert H. P. Oude Essink; Pieter S. Pauw; Perry G. B. de Louw; Anton Leijnse; Sjoerd E. A. T. M. van der Zee (Water Resources Management, 2017)

Review of Fusarium species isolated in association with mango malformation in Australia - E. C. Y. Liew; M. H. Laurence; C. A. Pearce; R. G. Shivas; G. I. Johnson; Y.P. Tan; J. Edwards; S. Perry; A.W. Cooke; B. A. Summerell (Australasian Plant Pathology, 2016)

Phenotypic variation and identification of quantitative trait loci for ozone tolerance in a Fiskeby III × Mandarin (Ottawa) soybean population - Amy L. Burton; Kent O. Burkey; Thomas E. Carter; James Orf; Perry B. Cregan (Theoretical and Applied Genetics, 2016)

Confirmation of delayed canopy wilting QTLs from multiple soybean mapping populations - Sadal Hwang; C. Andy King; Jeffery D. Ray; Perry B. Cregan; Pengyin Chen; Thomas E. Carter; Zenglu Li; Hussein Abdel-Haleem; Kevin W. Matson; William Schapaugh; Larry C. Purcell (Theoretical and Applied Genetics, 2015)

The Influence of Freshwater on Nekton Community Structure in Hydrologically Distinct Basins in Northeastern Florida Bay, FL, USA - Kerry E. Flaherty; Richard E. Matheson; Robert H. McMichael; William B. Perry (Estuaries and Coasts, 2013)

A conceptual framework for predicting temperate ecosystem sensitivity to human impacts on fire regimes - D. B. McWethy; P. E. Higuera; C. Whitlock; T. T. Veblen; D. M. J. S. Bowman; G. J. Cary; S. G. Haberle; R. E. Keane; B. D. Maxwell; M. S. McGlone; G. L. W. Perry; J. M. Wilmshurst; et al. (Global Ecology and Biogeography, 2013)
Aim The increased incidence of large fires around much of the world in recent decades raises questions about human and non‐human drivers of fire and the likelihood of increased fire activity in the future. The purpose of this paper is to outline a conceptual framework for examining where human‐set fires and feedbacks are likely to be most pronounced in temperate forests world‐wide and to establish and test a methodology for evaluating this framework using palaeoecological records. Location T asmania, north‐western USA , southern S outh A merica and N ew Z ealand. Methods We outline a conceptual framework for predicting the sensitivity of ecosystems to human impacts on fire regimes and then use a circum‐ P acific comparison of existing historical reconstructions of fire, climate, human settlement and vegetation to evaluate this approach. Results Previous research investigating important controls on fire activity shows that the sensitivity of temperate ecosystems to human‐set fires is modulated by the frequency of natural fire occurrence, fuel moisture and fuel type and availability. Palaeoecological data from four temperate regions suggest that the effects of anthropogenic burning are greatest where fire is naturally rare, vegetation is poorly adapted to fire and fuel biomass is abundant and contiguous. Alternatively, where fire activity is naturally high and vegetation is well adapted to fire, evidence of human influence on fire and vegetation is less obvious. Main conclusions Palaeofire records suggest that the most dynamic and persistent ecosystem transitions occur where human activities increase landscape flammability through fire–vegetation feedbacks. Rapid forest transitions in biomass‐rich ecosystems such as N ew Z ealand and areas of Tasmania and southern South America illustrate how landscapes experiencing few fires can shift past tipping points to become fire‐prone landscapes with new alternative stable state communities. Comparisons of palaeoecological data from different regions with similar biophysical gradients but different human settlement histories can provide new opportunities for understanding ecosystem vulnerability to fire–climate–human interactions.

Primary Productivity in 20-year Old Created Wetlands in Southwestern Virginia - Robert B. Atkinson; James E. Perry; Gregory B. Noe; W. Lee Daniels; John Cairns (Wetlands, 2010)

High-throughput genotyping with the GoldenGate assay in the complex genome of soybean - David L. Hyten; Qijian Song; Ik-Young Choi; Mun-Sup Yoon; James E. Specht; Lakshmi K. Matukumalli; Randall L. Nelson; Randy C. Shoemaker; Nevin D. Young; Perry B. Cregan (Theoretical and Applied Genetics, 2008)

Marcy: A chipping variety with resistance to common scab and the golden nematode - Walter S. De Jong; Donald E. Halseth; Bill B. Brodie; Keith L. Perry; Joseph B. Sieczka; Barbara J. Christ; Gregory A. Porter; Ken M. Paddock; Michael W. Peck; Robert L. Plaisted (American Journal of Potato Research, 2006)

Vegetation Communities of 20-year-old Created Depressional Wetlands - Robert B. Atkinson; James E. Perry; John Cairns (Wetlands Ecology and Management, 2005)

Impulsivity (delay discounting) as a predictor of acquisition of IV cocaine self-administration in female rats - Jennifer L. Perry; Erin B. Larson; Jonathan P. German; Gregory J. Madden; Marilyn E. Carroll (Psychopharmacology, 2005)

DNA sequence analysis identifies genetically distinguishable populations of harp seals ( Pagophilus groenlandicus ) in the Northwest and Northeast Atlantic - E. A. Perry; G. B. Stenson; S. E. Bartlett; W. S. Davidson; S. M. Carr (Marine Biology, 2000)

Biologically active compounds from Ozothamnus leptophyllus - Jacqueline E. Wood; Murray H. G. Munro; John W. Blunt; Nigel B. Perry; John R.L. Walker; Josephine M. Ward (New Zealand Journal of Botany, 1999)
A crude extract from a New Zealand native plant, Ozothamnus leptophyllus , was shown to possess antifungal activity. Flavonoids, mainly chalcones in the leaf exudate, were isolated, some of which possessed antiviral as well as antifungal activity. These flavanoids are excreted by glandular trichomes and form quasi‐crystalline deposits on the abaxial side of the leaves. 2’,4’,6'‐Trihydroxy‐chalcone was found to be active against both Polio virus (Pfizer vaccine strain) and Herpes simplex type 1 (ATCC VR 733); it was also responsible for anti‐dermatophytic activity against Trichophyton mentagrophytes . 2’,4'‐Dihydroxy‐4'‐methoxy‐dihydrochalcone was also active against both viruses.

The 10th Conference of the Entomological Society of Israel - Rachel Galun; I. Ishaaya; Sara Yablonski; Zmira Mendelson; Y. Mansour; Svetlana Kontsedalov; U. Pluschkell; A. R. Horowitz; A. R. Horowitz; Sara Yablonski; Zmira Mendelson; I. Ishaaya; et al. (Phytoparasitica, 1997)

s of papers presented at the Forty-First annual meeting - Jay L. Haddock; Ray D. Jackson; W. O. Harrington; R. L. Olson; W. J. Weston; Mary L. Belote; W. J. Hooker; A. P. Benson; R. W. Hougas; S. J. Poloquin; R. W. Ross; G. V. C. Houghland; et al. (American Journal of Potato Research, 1958)